Frontal Fibrosing Alopecia and Sunscreen Use: A Cross-sectional Study of Actinic Damage - María Librada Porriño-Bustamante; Trinidad Montero-Vílchez; Fernando Javier Pinedo-Moraleda; Ángel Fernández-Flores; María Antonia Fernández-Pugnaire; Salvador Arias-Santiago (Medical Journals Sweden, 2022)
Patients with frontal fibrosing alopecia report higher rates of sunscreen use than control subjects. However, it is not known whether the higher use of sunscreens is a cause or a consequence of the alopecia. A greater use of sunscreens should be associated with a lower incidence of signs of actinic damage. The aim of this study is to assess the presence of actinic damage in patients with frontal fibrosing alopecia. A cross-sectional study was carried out on 101 patients with frontal fibrosing alopecia and 40 control subjects. The presence of actinic damage, in the form of solar lentigines, actinic keratoses, and basal and squamous cell carcinomas, was recorded in both groups, together with sunscreen use. Trichoscopy and skin biopsy were performed on patients. Actinic damage was present more frequently in patients with frontal fibrosing alopecia (69.3%) than in control subjects (50%) (p = 0.031). Patients used sunscreens more frequently than did control subjects (83.2% vs 62.5%, p = 0.008). However, the prevalence of trichoscopic inflammatory signs, peripheral alopecia, and inflammatory infiltrate and sebaceous gland involvement in skin biopsy, were similar in patients who used sunscreens and those who did not use them. In conclusion, patients with frontal fibrosing alopecia had greater actinic damage than did control subjects, and this is hypothesized as a reason for the higher use of sunscreens among patients. Thus, use of sunscreens may not be the trigger for frontal fibrosing alopecia that dermatologists have proposed.